Assessment of preference Liriomyza spp. in different chickpea genotypes and effect of Melia azedarach L. extract: preliminary results - Ávalos, Delia S.; Ricobelli, Guillermo; Palacios, Sara M.; Defagó, María T. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
In Argentina several genotypes of chickpea (Cicer arietinum L.) have been developed to be cropped in environmentally different production areas. These have different phenotypes which could affect oviposition preferences of the behavior of leafminer. The aims of this study were two-fold: 1) to determine if leafminer Liriomyza spp. has a preference for any chickpea genotype, and 2) to evaluate the insecticide effect of Melia azedarach extracts on susceptible genotypes. Two selected lines and two cultivars of C. arietinum were planted in the experimental field of the FCA, UNC, in randomized blocks with three replications. Through weekly surveys, the preference of the flies in the period from July to September was determined by recording their presence in plants. The leafminer significantly choice the genotype with entire and large leaves. Subsequently, they were treated with botanical extracts by selecting five plants on each block: fifteen of them were treated with a 10% M. azederach extract and the other fifteen only with water (control). Number of mined leaves, pupae and emerged adults decreased after the treatment with the extract. Additional studies are needed to consider this natural compound in a management plan for the herbivore.